The effectiveness of garlic extract against Spodoptera litura on Chili - Firmansyah, Efrin; Hidayat, Cecep; Roosda, Anna Aina; Pradana, Adinda Nurul Fatah Adi; Soelistijono, R (Kultivasi, 2023)
Spodoptera litura is a polyphagous pest and attack many families of cultivated plants, such as chili plants. Application of synthetic pesticides is still the mainstay for controlling this pest in the field. To support eco-friendly plant protection management, it is important to explore potential natural materials such as garlic extract. This research aims to determine the potential of garlic extract in controlling S. litura on chili plants, and to see its indirect effect on chili yield. The research was carried out in two sites, in the laboratory and the field. The experiment used a completely randomized design with 6 treatments and 4 replications. The concentrations of garlic extract, i.e., control (0%), 24%, 26%, 28%, 30%, and 32%. The results showed the application of garlic extract had a significant effect on the mortality of S. litura, the frequency of attacks, and the intensity of pest attacks in the field, and had an effect on the variable number of fruit and fruit weight of chili plants. The LC50 and LC90 values reached 19.66% and 29.97% in the laboratory, and 28.30% and 34.3%% in the field, respectively. The LT50 and LT90 values from the 32% garlic extract in the laboratory were respectively 3.37 and 7.23 days. The application of garlic extraction affected growth and yield, i.e. healthy leaves, number of fruits, and weight of fruits in chili. The garlic extract is potentially used as an organic pesticide to suppress the S.litura attacks while keeping the plant's growth and yield.